FRI0296 Diagnostic performance of salivary gland ultrasonography in the early stages of pss in a real-life clinical setting. (23rd January 2014) - Luciano, N.; Baldini, C.; Pascale, R.; Sernissi, F.; Martini, D.; Carli, L.; Ferro, F.; Notarstefano, C.; Tani, C.; Talarico, R.; Mosca, M.; Bombardieri, S.
Abstract : Background: Recently, convincing data have been published on the diagnostic value of salivary gland ultrasonography (SGUS) in primary Sjögren's syndrome (pSS). A limited number of information are available on the performance of SGUS in the early stages of the disease Objectives: The purposes of this single-center study were: a. To explore the performance of SGUS in a cohort of unselected patients with suspected pSS and duration of sicca symptoms ≤ 5 years; b. To correlate the SGUS score to other tests included among the AECG criteria for assessing salivary gland involvement in pSS (i.e. minor salivary gland biopsy focus score (MSGB/FS) and salivary flow rate measured by sialometry) Methods: The study population consisted of consecutive unselected patients with dry eye and dry mouth suggestive for pSS and symptoms duration ≤ 5 years. A standardized clinical, serological and histological diagnostic algorithm for pSS was performed in all the cases according to the AECG criteria. Unstimulated whole saliva was collected under standard conditions at the study inclusion according to the AECG sialometry protocol. US of salivary glands was performed by the same radiologist blinded to the diagnosis and the following US parameters were recorded: size, parenchymal echogenicity and inhomogeneity in the parotid and submandibular glands on both sides. A previously reported ultrasound scoring system (De Vita et al 1992) was used to grade the echostructure alterations of the salivary glands. SGUS findings were correlated to patients' clinical and serological features, to the MSGB/FS and to the patients' unstimulated whole salivary flow rate. Results: Thirty-two female patients were enrolled in this study from March 2012 and December 2012 (age=53±15, mean ±SD, years; duration between onset of symptoms and time of diagnosis = 2.1±1.8, mean ± SD, years). Twenty-two patients met the AECG criteria for pSS and 10/32 who did not fulfill the AECG criteria represented the control group. Patients with pSS showed a significantly higher SGUS score in comparison with controls (1.8±1.6 vs 0.4±1.0, p<0.05). The sensitivity of the SGUS score was 55% and the specificity was 90%. An inverse correlation was observed between the SGUS score and the age of the patients (r=-40, p=0.02) with younger patients frequently presenting multiple hypoechogenic areas especially in the parotids. A significant correlation was also found between the SGUS score and the MSGB/FS (r=37, p=0.05). No correlation was detected between the salivary gland echostructure grading and the unstimulated salivary flow rate. Conclusions: This study confirmed that, despite the low sensitivity, SGUS might represent a specific non-invasive tool for the diagnosis of pSS in the early stages of the disease. Further research in larger cohort of patients is mandatory in order to better clarify the role of SGUS in the diagnostic algorithm of pSS Disclosure of Interest : None Declared